Success of large felines breeding in captivity, a studbook review - Morein, Lina (SLU/Dept. of Animal Environment and Health (until 231231), 2013)
In the past there has not been much concern about the breeding of exotic animals in captivity since many of the species kept could be replenished from the wild if needed. After years of collecting wild specimen for zoos the animals have begun to disappear from the wild and become threatened or endangered which makes it unsustainable to continue this practice. The number of techniques for captive breeding have increased tremendously over the years and research on breeding has progressed rapidly. The breeding of exotic species in captivity as a means of saving the threatened wild population has increased over the years. For many species reproducing under captive conditions has been difficult as well as obtaining surviving offspring. Although, of the three species chosen for this study, only the cheetah (Acinonyx jubatus) has had difficulty with breeding in captivity. This study was conducted to observe how the breeding of cheetahs (A. jubatus), tigers (Panthera tigris), and lynx (Lynx lynx) have been in the last ten years and see if any conclusion can be drawn. Although there has been some cubs which has died before six months of age, the statistics has gotten better as the years have progressed. For the future it would be recommended that more consideration be paid towards the animals’ natural breeding behaviour. Many of the problems faced are due to inadequate housing or social environment. Efforts must also be put on evolving the modern zoo into something that not only preserves the animals but also improves on its work on educating the public.